Direct and indirect impacts of different water regimes on the invasive plant, alligator weed (Alternanthera philoxeroides), and its biological control agent, Agasicles hygrophila. Issue 1 (21st October 2014) - Wei, Hui; Lu, Xinmin; Ding, Jianqing
Abstract : Invasive weeds are broadly affected by natural disturbances, such as flooding and drought. While these disturbances can directly affect the outcome of a plant invasion, they can also indirectly affect the population dynamics of the invasive plant's natural enemies. However, how flooding and drought alter the interactions of invasive plants with their natural enemies and what impact these events have on the invasive plants have been little studied. This study reports on the effects of flooding and drought on the invasive plant, Alternanthera philoxeroides, its biological control agent, Agasicles hygrophila, as well as their interactions in field and laboratory experiments. It was found that drought decreased the stem length and number of internodes of A. philoxeroides, while flooding reduced the number of branches, relative to those in the control treatments. Both drought and flooding significantly decreased the total number of ramets, as well as the root and shoot mass of this weed, compared to a less drastic water regime. Drought indirectly suppressed the population growth of Ag. hygrophila by decreasing plant palatability. Indeed, herbivory by Ag. hygrophila had little impact on A. philoxeroides under drought conditions. The results of this study suggest that drought can reduce the biological control of A. philoxeroides indirectly by interrupting plant–insect interaction. Therefore, understanding how invasive plants and enemies interactively respond to seasonal climatic disturbances will provide important information for improving and predicting the management efficiency of invasive weeds.